Trajectory - Russo, Richard, 1949- (Alfred A. Knopf, 2017)
"In this pair of novellas and two stories, Russo's characters bear little similarity to the blue-collar citizens we're familiar with from most of his novels. In "Horseman," a tenured professor confronts a young plagiarist as well as her own weaknesses asthe Thanksgiving holiday approaches--"And after that, who knew?" In "Intervention," a realtor facing an ominous medical prognosis finds himself in his father's shadow while he presses forward, or not. In "Voice," a semi-retired English professor is connedby his increasingly estranged brother into coming along on a group tour of the Biennale, fleeing a mortifying incident with a traumatized student back in Massachusetts but encountering further complications en route. And in "Milton and Marcus," a lapsednovelist is struggling with his wife's illness and trying to rekindle his screenwriting career, only to be stymied by the pratfalls of that trade when he's called to an aging, iconic star's mountaintop in Wyoming"--